2010
DOI: 10.1371/journal.pone.0010437
|View full text |Cite
|
Sign up to set email alerts
|

Potential Costs of Acclimatization to a Warmer Climate: Growth of a Reef Coral with Heat Tolerant vs. Sensitive Symbiont Types

Abstract: One of the principle ways in which reef building corals are likely to cope with a warmer climate is by changing to more thermally tolerant endosymbiotic algae (zooxanthellae) genotypes. It is highly likely that hosting a more heat-tolerant algal genotype will be accompanied by tradeoffs in the physiology of the coral. To better understand one of these tradeoffs, growth was investigated in the Indo-Pacific reef-building coral Acropora millepora in both the laboratory and the field. In the Keppel Islands in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
206
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 46 publications
9
206
3
Order By: Relevance
“…It is well established that distinct zooxanthellae phenotypes have different metabolic demands (Fitt, 1985). It is interesting to note that corals harbouring "stress" tolerant clade D1 zooxanthellae have reduced skeletal growth rates (Jones and Berkelmans, 2010); which has been interpreted as meaning that D1 is a suboptimal symbiont, despite its stress tolerance (Jones and Berkelmans, 2010). The new biomineralisation model suggests caution with this inference, since the lower skeletal growth rates may actually indicate that the coral host is undertaking less "work" to maintain the benefits of the established symbiosis.…”
Section: Symbiont Metabolismmentioning
confidence: 99%
“…It is well established that distinct zooxanthellae phenotypes have different metabolic demands (Fitt, 1985). It is interesting to note that corals harbouring "stress" tolerant clade D1 zooxanthellae have reduced skeletal growth rates (Jones and Berkelmans, 2010); which has been interpreted as meaning that D1 is a suboptimal symbiont, despite its stress tolerance (Jones and Berkelmans, 2010). The new biomineralisation model suggests caution with this inference, since the lower skeletal growth rates may actually indicate that the coral host is undertaking less "work" to maintain the benefits of the established symbiosis.…”
Section: Symbiont Metabolismmentioning
confidence: 99%
“…Partner-switching following a bleaching event may occur by recovery with different symbionts that are better suited to the prevailing conditions [4,11], an idea termed the Adaptive Bleaching Hypothesis (ABH; 'adaptive' referring to a beneficial trait that can be positively selected for; [12]). In particular, recovery with heat-tolerant symbionts can increase resistance to future thermal bleaching [8], but at a potential energetic cost [13][14][15][16]. Investigations of the ABH have revealed that, although corals sometimes change their symbionts [8,9,[17][18][19][20][21], this does not always occur: sometimes corals recover with the same symbiont community they had prior to stress [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1). However, the relative importance of different symbionts to the holobiont's resilience is difficult to assess due to complex interactions and trade-offs (Fitt et al, 2001;Abrego et al, 2008;Fitt et al, 2009;Jones and Berkelmans, 2010). Moreover, while some intracellular sites and effects of thermal damage in the host and symbiont have been identified, there is no consensus about the causal chain of events and the supposed 'weak link' in the symbiosis.…”
Section: Introductionmentioning
confidence: 99%